The missing puzzle piece in translation pedagogy: Adaptive and elastic competence - Zhang, Grace (The Chinese University Press, 2012)
The study of effective and innovative translation pedagogy has been drawing increasing attention in recent years, but the training of adaptive and elastic competence is somewhat overlooked. This study investigates the importance of strategic translation through the theoretical lens of Verschueren's (1998) Adaptation Theory. The analysis is based on a case study of the 2001 Sino-American Hainan airplane collision crisis, and in particular the pivotal role of different versions of the American "two sorries" letter in facilitating the resolution. It highlights the need to incorporate language adaptation and the interests of all parties in a translation. This study argues that translation is a negotiable and adaptable process, influenced by both overt and covert components, and that this process should be reflected in translation education by foste1ing the ability to get behind the text to cater to the interests of all interested parties: that is, to cultivate adaptive and elastic competence. The findings suggest that a realistic, balanced, and robust account of adaptation and elasticity is needed for effective translation education.